Proceedings of the 33rd ACM/IEEE International Conference on Automated Software Engineering 2018
DOI: 10.1145/3238147.3238183
|View full text |Cite
|
Sign up to set email alerts
|

A large-scale study of test coverage evolution

Abstract: Statement coverage is commonly used as a measure of test suite quality. Coverage is often used as a part of a code review process: if a patch decreases overall coverage, or is itself not covered, then the patch is scrutinized more closely. Traditional studies of how coverage changes with code evolution have examined the overall coverage of the entire program, and more recent work directly examines the coverage of patches (changed statements). We present an evaluation much larger than prior studies and moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 34 publications
0
23
0
1
Order By: Relevance
“…Memon and Cohen [26] described multiple negative effects that flaky tests can create, discovering that their occurrence may even lead to features not being included in a release as they were not able to be tested sufficiently beforehand [26]. Marinescu et al [25] and Hilton et al [20] analyzed the evolution of test suite coverage, reporting that the presence of flaky tests produces an intermittent variation of the branch coverage.…”
Section: Related Workmentioning
confidence: 99%
“…Memon and Cohen [26] described multiple negative effects that flaky tests can create, discovering that their occurrence may even lead to features not being included in a release as they were not able to be tested sufficiently beforehand [26]. Marinescu et al [25] and Hilton et al [20] analyzed the evolution of test suite coverage, reporting that the presence of flaky tests produces an intermittent variation of the branch coverage.…”
Section: Related Workmentioning
confidence: 99%
“…Moonen et al have shown that about 2/3 of the refactoring changes from Fowler et al (1999) can actually result in non-building test cases because the refactoring changes the original interface and the test code requires a change in the types of classes that were involved in the refactoring (Moonen et al 2008). In contrast, Hilton et al have recently performed a study on test coverage evolution using Continuous Integration builds (Beller et al 2017), reporting that this modern infrastructure eases building prior versions of a software project considerably (Hilton et al 2018). We could consider implementing these perfect tests by automatically generating them, e.g., using EvoSuite (Fraser and Arcuri 2013a;Palomba et al 2016).…”
Section: Limitations and Solutionsmentioning
confidence: 99%
“…COVERALLS also provides an API in which it made available information about the branch, the total coverage, and the change in the coverage in a particular build. The data available on COVERALLS have also be used in other studies (e.g., [17]).…”
Section: Rq4: How Common Are Long Running Builds?mentioning
confidence: 99%
“…However, this is often non-trivial task (e.g., some projects fail, some projects require manual configuration, etc). Since recent related work is also employing COVERALLS (e.g., [17]), we opted to use the COVERALLS infrastructure to gather coverage information for this work as well.…”
Section: Threats To Validitymentioning
confidence: 99%